2000
DOI: 10.1007/s002800000140
|View full text |Cite
|
Sign up to set email alerts
|

Combined cytotoxic action of paclitaxel and ceramide against the human Tu138 head and neck squamous carcinoma cell line

Abstract: Our results suggest that paclitaxel/ceramide combination therapy may be an attractive alternative to conventional methods of chemotherapy for head and neck cancer, and should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 0 publications
0
42
0
2
Order By: Relevance
“…It is known that increased ceramide generation in response to various stress stimuli including radiation and chemotherapeutic agents, or treatment with exogenous ceramides, can result in the inhibition of growth and/or induction of cell death in various cancer cells in situ (5 -8). Indeed, the role for exogenous ceramide against HNSCC growth was shown previously, which showed that the combination of paclitaxel and C 6 -ceramide synergistically decreased the growth of the human Tu138 HNSCC cells (9). Similarly, in an independent study, the inhibition of growth in various HNSCC cell lines, but not in normal keratinocytes, by treatment with a recently developed L-threo-C 6 -pyridinium ceramide with high bioavailability and bioactivity was reported (10).…”
Section: Introductionmentioning
confidence: 62%
“…It is known that increased ceramide generation in response to various stress stimuli including radiation and chemotherapeutic agents, or treatment with exogenous ceramides, can result in the inhibition of growth and/or induction of cell death in various cancer cells in situ (5 -8). Indeed, the role for exogenous ceramide against HNSCC growth was shown previously, which showed that the combination of paclitaxel and C 6 -ceramide synergistically decreased the growth of the human Tu138 HNSCC cells (9). Similarly, in an independent study, the inhibition of growth in various HNSCC cell lines, but not in normal keratinocytes, by treatment with a recently developed L-threo-C 6 -pyridinium ceramide with high bioavailability and bioactivity was reported (10).…”
Section: Introductionmentioning
confidence: 62%
“…The clinical potential for the delivery of C 6 with additional therapeutic agents in liposomal vesicles is significant. Studies have shown that ceramide may act synergistically with chemotherapeutic agents, such as paclitaxel (54) and fenretinide (55). Thus, delivery of chemotherapeutic agents in C 6 -formulated liposomes may further enhance apoptotic actions.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of Paclitaxel are linked to the de novo synthesis of ceramide in MDA-MB-468 and MCF-7 breast cancer cells. Furthermore, Paclitaxel-dependent cytotoxicity is abrogated by blocking ceramide production with L-cycloserine, an inhibitor of ceramide synthesis (Mc Closkey et al, 1996;Mehta et al, 2000). Tamoxifen, a triphenylethylene antiestrogen, blocks the conversion of ceramide to glucosylceramide, thereby promoting an increase in cellular ceramide concentration (Cabot et al, 1996;Lavie et al, 1997).…”
Section: Ceramide and Cancermentioning
confidence: 99%